ANALYZING EMPLOYEE COMMITMENT TO EMPLOYMENT SERVICE PROVIDER COMPANY (CASE STUDY OF PT. INTRIAS MANDIRI SEJATI IN MANADO) - Tirajoh, Kenny Monica; Saerang, David P.E; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Organizations have realized that performance of their employees determines the success of the organization. It is including of how the workers act in the organization or manage their behavior. Organizational behavior can help people to investigate the impact that individuals, groups, and structures have on behavior within the organization in order to improve the effectiveness of the organization. It is important for managers to know how to get the best of their workersâ€™ performance through employee commitment. The research aims to analyse commitment of the employees to employment service provider company PT. Intrias Mandiri Sejati as outsourcing employees supplied to business partners. This research is a qualitative research using case study method based on primary data from an in-depth interview of 11 informants as the sample who were chosen by using purposive and snowball sampling technique. This result that was concluded from the three dimensions of employee commitment based on employee mind-set: affective commitment, continuance commitment, and normative commitment, shows that the employees are in a good commitment to provider company and business partners. This study suggest the company to maintain its level of attentiveness regarding employee commitment, because commitment is a determinant of the employee performance in the company.Keywords: employee commitment, affective commitment, continuance commitment, normative commitment, employment service provider company.Â